C2 Solitary Bone Plasmacytoma Curettage and Vertebral Augmentation in an 83-Year-Old Female: Case Report and Review of Surgical Treatment Approaches in the Spine - Matthew J. Yousif; Taha A. Faruqi; Rakesh Ramakrishnan; Nilesh M. Patel (Case Reports in Orthopedics)
Surgically, solitary bone plasmacytoma (SBP) of the craniocervical junction (CCJ) is typically treated with cement augmentation and occipital-cervical stabilization (OCS). In the orthopedic spine literature, various surgical treatment options have been described for SBP, but only a few studies exist describing SBP of the CCJ with treatment involving cement augmentation alone. We report the case of an 83-year-old female found to have C2 SBP that was successfully treated with curettage and cement augmentation alone.